ANALISIS KESESUAIAN LAHAN REHABILITASI MANGROVE DI KECAMATAN BONTOA KABUPATEN MAROS PROVINSI SULAWESI SELATAN - Saru, Amran (Torani Journal of Fisheries and Marine Science, 2016)
Mangrove ecosystem is one of the coastal ecosystem has a very important role, because it has a physicalfunction, bioekologis and economical for coastal communities. Currently the mangrove suffered damage fromthe severe pressure due to population growth. To reduce the damage it is necessary to mangrove rehabilitation,one of the factors to consider are suitability rehabilitation. This study aims to analyze and map the suitability ofmangrove rehabilitation area in District Bontoa Maros South Sulawesi. Benefit from the results of this study,expected to provide information on the analysis of land suitability for Rehabilitation magrove. This researchwas conducted in March 2011. The method used is survey method with parameters Field current conditions,tides, waves, temperature, salinity, substrate conditions, and slope. Data analyzed by the scoring method andplotted based on the map. Results of this study showed two categories namely accordance suitability andsufficient appropriate, categorized according to the type of Rhizophora spp, Avicennia spp, Sonneratia alba, S.caseolaris, Bruguiera parvilofa and B. Xesangula and B. gymnorhiza. Conditions mangrove areal extents thatcan be rehabilitated at each study site: Ampelkale village of 55.375 ha, 6.636 ha Pajukuang village, and thevillage of Bontobahari 16.011 Ha.Keywords: Land suitability and Rehabilitation of Mangrove Ecosystem.